Virtuţile şi limitele deliberării: o analiză critică a „turnurii deliberative” din teoria democraţiei - Tutui Viorel (Argumentum: Journal of the Seminar of Discursive Logic, Argumentation Theory and Rhetoric, 2010)
Abstract: In the last two decades the theory of democracy took a „deliberative turn”: a shift in the controversies in this field from the traditional models of democracy, based on voting and representation, to a model that promotes the ability of all individuals subject to a collective decision to engage in authentic deliberation about that decision. In this paper I present and analyze the main issues concerning this shift in the attempt to answer the following questions: What is the “deliberative turn” and how is it justified? Which are the most important deliberative theories of democracy? Which are the main difficulties that they face?